Colorado Boulevard - Sutton, Phoef (A Crush novel, 2017)
"When Zerbe, the honorary brother (and roommate) of LA's toughest bodyguard/bouncer, Crush, is kidnapped, Crush springs into action to save him. Unraveling the mystery takes him to Zerbe's estranged billionaire father, who's obsessed with building California's long-promised bullet train, as well as to Pasadena's famed Rose Parade along Colorado Boulevard. Rich with witty dialogue, nonstop action, and a solid mystery"--